Problem of criminal liability for declaring false information - Шама, Р. І. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2017)
Effective prevention and counteraction to corruption is one of the most important problems of our time. On October 14, 2014, the Verkhovna Rada of Ukraine adopted a number of anti-corruption laws aimed at reforming anti-corruption system according to European standards. Observation and enforcement of these particular regulations by government agencies raises many questions regarding their effectiveness. The Law of Ukraine «On prevention of corruption» incorporated into the Criminal Code a new article (366–1), which introduced the concept of crime in the area of service and professional activities related to the provision of public services – declaring false information. The work is devoted to the analysis of the validity of the criminalization of Article 366–1 of the Criminal Code of Ukraine, determination of the practical and theoretical significance. The problems and shortcomings that arose with the introduction of changes to the current legislation were analyzed and recommendations for better efficiency were suggested. Amendments suggested to the Article 366–1 of the Criminal Code of Ukraine, will promote the effectiveness of this article in practice and eliminate the possibility of the subjects of the declaration refer to arithmetic errors while completing the declaration.

У роботі здійснюється аналіз обґрунтованості криміналізації статті 366–1 Кримінального кодексу України (далі – КК України), визначення її практичного та теоретичного значення. Досліджуються проблеми й недоліки, що виникли у зв’язку з внесенням змін до чинного законодавства, а також пропонуються пропозиції щодо їх усунення.
ПРОБЛЕМА КРИМІНАЛІЗАЦІЇ ДЕКЛАРУВАННЯ НЕДОСТОВІРНОЇ ІНФОРМАЦІЇ
Keywords: preventing corruption; declaring; false information; the subject of declaration.; запобігання корупції; декларування; недостовірна інформація; суб’єкт декларування.